EVALUASI KEKERASAN RESTORASI NIKEL-KROMIUM DENGAN BERBAGAI METODE CASTING - Soesetijo, FX Ady (Fakultas Kedokteran Gigi Universitas Jember, 2012)
Non precious alloys were used widely in dentistry, because cost was relatively lower than noble alloys (precious alloy). This study aims to evaluate the microhardness NiCr alloys were frequently used in the construction of crown and bridges prosthodontics and metal frame dentures with different methods. Casting methods used were: 1) induction / argon, the argon electromagnetic induction with controlled atmospheric pressure, 2) induction / vacuum, the electromagnetic induction in a vacuum environment, 3) induction /air, electromagnetic induction air was not controlled by atmospheric pressure and 4) flame / air from combustion of gas / oxygen in centrifugal castings machine was not controlled by atmospheric pressure. The three of alloys used were Ni-Cr-Mo-Ti: Ni-Cr-Mo-Be and Ni-Cr-Mo-Nb. The sample size was 60, divided into 12 groups (each group consisted of 5 samples). Cylindrical samples with a length of 15 mm and a diameter of 1.6 mm. After casting, the samples were embedded in resin and polished for Vickers microhardness measurement in a Shimadzu HMV-2 (1000 g with duration of 10 seconds). The data obtained were in the form of indentations (indentation) on the surface of the sample. The data was subjected to two-way ANOVA and Tukeys multiple comparison test ( = 0.05). The two way ANOVA suggested a non significant effect of the interaction alloys versus casting (p=0.10). A significant effect of alloy (p<0.0001)and casting methods (p<0,0001) was detected. The hardness value of Ni-Cr-Mo-Ti (421 ± 7.8) was higher (p <0.05) than the Ni-Cr-Mo-Nb (414 ± 7.6). The hardness value of the casting method of induction / argon and induction/ vacuum was similar (p> 0.05), and lower than the induction / air and flame / air (p <0.05). The lowest hardness value was Ni-Cr-Mo-Be (358 ± 10.7). The hardness value in the condition induction/ air and flame /air was similar (p> 0.05). The microhardness of the alloys was influenced by their composition and casting method. The microhardness of NiCr alloy hardness was higher when they were cast with induction/air and flame/air methods